Association Between Resting Heart Rate and the Risk of Incident Hypertension Among Older Chinese Adults: A Prospective Cohort Study - Shiyu Lou; Zihan Yu; Yizhu Song; Dechen Liu (The Journal of Clinical Hypertension)
ABSTRACT Examining the role of resting heart rate (RHR) in hypertension risk could improve our understanding of its pathogenesis. However, most relevant studies have been conducted in developed countries such as the United States and Brazil, with no evidence for the older Chinese population. Therefore, this study aimed to investigate the association between RHR and the risk of developing hypertension in an older Chinese population. A total of 3836 participants from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) were included in this prospective study. Using Cox proportional hazard models, the association between RHR and the risk of incident hypertension was evaluated, with results expressed as hazard ratios (HRs) and 95% confidence intervals (CIs). Multiplicative interaction effects were analyzed for RHR with age, sex, and regular exercise, and subgroup analyses of the association were also conducted based on these factors. Sensitivity analyses were conducted to evaluate the robustness of the results. During a 4.86‐year follow‐up, 1449 incident cases of hypertension occurred. Every 10 beats per min increase in RHR was associated with a 6% higher risk of incident hypertension (HR = 1.06, 95% CI: 1.01–1.12). Subgroup analyses demonstrated significant associations in women, participants aged ≥80, and those who did not exercise regularly. The sensitivity analyses confirmed the consistency of these results. These findings indicate that a faster RHR is associated with a higher risk of incident hypertension in the older Chinese population, suggesting its potential use in identifying older individuals at greater risk of incident hypertension.